An Improved Runway Operation Capacity Model for V-Open Multirunway Airports in China - Zhiyuan Shen; Xinyu Xu; Yong He; YongGang Yan; Lin Zhou; Yingying Hu (Journal of Advanced Transportation)
Diverging runways are receiving considerable attention as replacements for parallel runways when constructing three or more runways in China. This has been prompted by the limitations associated with a single-direction airspace and associated regulations when using parallel runways. However, the operating efficiency of diverging runways is still greatly constrained by the separation standard for departing aircraft in CCAR-93TM-R5 and Decree of CAAC NO.123. To address these problems, an improved runway operation capacity model for a V-open multirunway airport is proposed to reduce the separation standard based on the equivalent lateral separation operation (ELSO) standard. A collision risk module is first proposed to assess the feasibility and safety of the proposed policy. Also, a novel runway capacity model for V-open multiple runways is then built to improve the operating efficiency for diverging runway. A series of comparative experiments based on actual flight data from Chengdu Tianfu International Airport demonstrated that reducing the divergence angle from 15° to 10° improved the runway operation capacity by about 8% based on the proposed improved policy. These research results could play a major role in facilitating appropriate amendments to the associated CAAC operation regulations.